Seasonal Variation in Land and Sea Surface Backscatter Coefficients at High Frequencies - Danielle Edwards; Manuel Cervera (Remote Sensing, 2022)
Over the horizon radars (OTHR) rely on the propagation of high frequency (HF) radio waves via the ionosphere to successfully achieve their designated missions. Backscatter sounders (BSS) are environmental over-the-horizon radars which may be used to assess the ionospheric propagation conditions. However, high power observed by a BSS may be due to either good ionospheric propagation, a high surface backscatter coefficient, or a combination of both. Hence, an understanding of the surface backscatter coefficients and their temporal variation is essential to fully understand the ionospheric propagation conditions. A database of surface backscatter coefficients over a decade was created using backscatter ionogram data from four backscatter sounders in Australia. The temporal variations in the backscatter coefficients were investigated and it was found that the land backscatter coefficients were relatively constant over time, while the sea backscatter coefficients showed significant seasonal variation.